Skin diseases among tea garden workers of Dibrugarh district, Assam: a cross-sectional study - Ahmed, Tanzil S.; Gogoi, Gourangie; Kotoky, Manas J.; Barua, Shyamanta (International Journal Of Community Medicine And Public Health, 2025)
Background: Skin diseases are one of the most neglected conditions worldwide, but they pose a significant public health concern, particularly among certain groups of populations, like agricultural workers and tea garden workers, due to their occupational and environmental risk factors. Despite its burden, there is limited data regarding the patterns and determinants of such conditions. Hence, the study aims to assess the burden of skin diseases and their risk factors among tea garden workers. Methods: A community-based cross-sectional study was conducted over one year using a multistage study design. The data collected were sociodemographic characteristics, occupational exposures, personal hygiene and sanitation-related factors. A clinical examination was conducted to diagnose the skin lesions and univariate and multivariate analysis was performed to assess their risk factors. Results: The study reported a high prevalence of skin diseases which included infectious, pigmentary and inflammatory lesions, with infectious lesions being the most commonly reported. Socio-demographic factors like type of family, number of family members and occupational exposure to chemicals like pesticides and sanitation and hygiene were the significant factors contributed to skin diseases. Conclusions: An integrated approach is required to reduce the burden of skin diseases, which includes addressing risk factors by improving living conditions, promoting sanitation and hygiene and strengthening workplace safety to reduce occupational exposure.